Academic Skills Advice Solving Quadratics A quadratic equation is one where the highest power is 2. E.g. 3𝑥 2 − 7𝑥 − 6 = 0 There are 3 ways of solving them and you can choose whichever method you prefer. Factorising: making 2 brackets. Formula: uses the quadratic formula. Completing the square: making 1 bracket (squared). This lesson will look at the methods of using the formula and completing the square. (See the next lesson for how to factorise.) Coefficients: Before you can solve quadratics it is important that you know what the word coefficient means as it will be used throughout this lesson. The coefficient of 𝑥 2 is the number in front of 𝑥 2 . The coefficient of 𝑥 is the number in front of 𝑥. etc E.g. 3𝑥 2 − 7𝑥 − 6 = 0 The coefficient of 𝑥 2 The coefficient of 𝑥 The coefficient of 𝑥 2 is 𝟑 The coefficient of 𝑥 is −𝟕 Always be careful to include the correct sign with the coefficient: (e.g. The coefficient of 𝑥 is – 𝟕 and not 𝟕). © H Jackson 2011 / ACADEMIC SKILLS 1 Using the Formula 𝑥= −𝑏 ± √𝑏 2 − 4𝑎𝑐 2𝑎 The above formula is used to solve a quadratic equation in the form: 𝒂𝒙𝟐 + 𝒃𝒙 + 𝒄 = 𝟎. Notice that to use this method the equation must always equal 0. It is good practice to get into the habit of writing down what 𝑎, 𝑏 𝑎𝑛𝑑 𝑐 are equal to and then substituting them into the formula. Examples: Use the formula to solve: 𝟐𝒙𝟐 + 𝟑𝒙 − 𝟓 = 𝟎 In the above: 𝑎=2 𝑏=3 𝑐 = −5 Substitute a, b and c into the formula (being careful to use the correct signs). 𝑥= 𝑥= 𝑥= 𝑥= −(3)±√(3)2 −4×(2)×(−5) 2×(2) Notice that every letter has been replaced by a bracket with the correct number in it. −3±√9+40 4 −3±√49 4 −3+7 4 or −3−7 4 5 𝑥 = 1 𝑜𝑟 𝑥 = − 2 Use the formula to solve: −𝟑𝒙𝟐 − 𝟓𝒙 − 𝟐 = 𝟎 In the above: 𝑎 = −3, 𝑥= 𝑐 = −2 −(−5)±√(−5)2 −4×(−3)×(−2) 2×(−3) 𝑥= 5±√25−24 −6 𝑥= 5±√1 −6 𝑥 = −1 or − © H Jackson 2011 / ACADEMIC SKILLS 𝑏 = −5, 2 3 2 Completing the Square To use this method you must always make sure that the coefficient of 𝑥 2 is 1. The method: Make the coefficient of 𝑥 2 = 1 Half the coefficient of 𝑥 Make a bracket with (𝑥+ half the coefficient of 𝑥) and square it. Subtract (half the coefficient of 𝑥)2 Rearrange and solve. The method might sound complicated but try it – it’s not as difficult as it looks. Examples: Solve: 𝒙𝟐 − 𝟔𝒙 + 𝟕 = 𝟎 by completing the square. Make the coefficient of 𝑥 2 = 1: 𝑥 2 − 6𝑥 + 7 = 0 (no change) Half the coefficient of 𝑥: −3 2 Make a bracket and square it. (𝑥 − 3) Subtract (half the coefficient of 𝑥)2: (𝑥 − 3)2 − 32 Rearrange and solve: (𝑥 − 3)2 − 32 + 7 = 0 (𝑥 − 3)2 − 9 + 7 = 0 Notice that it’s this bit that is subtracted. (𝑥 − 3)2 − 32 + 7 = 0 Don’t forget to include the original 7. (𝑥 − 3)2 − 2 = 0 (Tidy up) (𝑥 − 3)2 = 2 (Square root each side) 𝑥 − 3 = ±√2 (Rearrange) 𝑥 = ±√2 + 3 Remember there is a +ve and –ve answer. 𝑥 = 4.4 𝑜𝑟 𝑥 = 1.6 © H Jackson 2011 / ACADEMIC SKILLS 3 Solve: 𝟒𝒙𝟐 + 𝟏𝟔𝒙 − 𝟖 = 𝟎 by completing the square. Make the coefficient of 𝑥 2 = 1: 𝑥 2 + 4𝑥 − 2 = 0 (÷ everything by 4) Half the coefficient of 𝑥: 2 Notice that it’s this bit that is subtracted. (𝑥 + 2)2 − 22 − 2 = 0 2 Make a bracket and square it. (𝑥 + 2) Subtract (half the coefficient of 𝑥)2: (𝑥 + 2)2 − 22 Rearrange and solve: (𝑥 + 2)2 − 22 − 2 = 0 (𝑥 + 2)2 − 6 = 0 Don’t forget to include the original -2. (𝑥 + 2)2 = 6 𝑥 + 2 = ±√6 𝑥 = ±√6 − 2 𝑥 = 0.45 𝑜𝑟 𝑥 = −4.45 Solve: 𝟑𝒙𝟐 + 𝟕𝒙 − 𝟔 = 𝟎 by completing the square. Make the coefficient of 𝑥 2 = 1: 7 𝑥2 + 3 𝑥 − 2 = 0 (÷ everything by 3) Half the coefficient of 𝑥: (don’t let the fraction put you off, just carry on as normal) 7 6 7 2 Make a bracket and square it. (𝑥 + 6) Subtract (half the coefficient of 𝑥)2: (𝑥 + 6) − (6) − 2 Rearrange and solve: (𝑥 + ) − 7 2 7 2 7 2 121 6 36 7 2 121 (𝑥 + 6) = 7 =0 36 121 𝑥 + 6 = ±√ 36 121 7 𝑥 = ±√ 36 − 6 𝑥 = 0.67 𝑜𝑟 𝑥 = −3 © H Jackson 2011 / ACADEMIC SKILLS 4